P03.04 Observational, prospective study on complications and tolerability of PICC (central venous catheter with peripheral insertion) in neurooncological patients. (19th September 2018) - Simonetti, G; Sommariva, A; Basso Ricci, C; Anghileri, E; Botturi, A; Eoli, M; Gaviani, P; Lamperti, E; Moreschi, C; Silvani, A
Abstract: Background: The use of central venous catheter with peripheral insertion (PICC) has increased rapidly in recent years particularly in cancer patients. However, the benefit provided may occasionally be affected by relevant complications. The precise incidence and risk of PICC related complications is unknown, as well as patients tolerability. The study aims to collect immediate, early and late complications related to PICC in neuro-oncological patients as well as evaluate the tolerability through semi-structured interviews. Material and Methods: Neuro-oncological patients at IRCCS Neurologico C. Besta, with PICC placed for normal clinical practice were consecutively included in the study. PICC related complications were recorded immediately (during the procedure), early (after 24 hours and within one week from placement) and late (after one week from placement and until the removal). All patients were also evaluated for tolerability through semi-structured interviews conducted after a week, 1 month, 3 months and 5 months from PICC placement. Results: 30 neurooncological patients have been enrolled. Chemotherapy regimens administered by the PICC were: fotemustine (73.3%), HDTMX (13.3%), bevacizumab (6.6%), PCV (6.6%). One week after PICC placement, 13.3% of patients presented hematoma (grade 1 CTCAE); 30% of the patients did not feel pain during the positioning procedure, in the remaining patients the average level of perceived pain was 2 (range 2–6), on a scale from 0 to 10. Regarding complications, 10% of patients showed the presence of semi-occludent /occluding thrombus as well as the presence of fibrin flaps. Only one infectious occurred (staphylococcal sepsis, grade 4 CTCAE). All events required removal of the device. In 6.6% of cases a dislocation of the PICC was recorded. One week after device placement, 94% of patients perceived the experience as "overall positive". Within one month, 78.5% of patients did not consider the device as a "foreign body". In 85.7% of cases, the PICC seems to give greater security during chemotherapy administration. In 57.1% of the cases PICC did not affect the habits related to hygiene or clothing (85.7%). In all cases, there were no difficulties while sleeping. Conclusion: The data obtained from the study will allow to implement corrective actions in order to reduce specific complications. Regarding tolerability, the device seems to be positively accepted in the majority of interviewed patients, without affecting the activities of daily life.